El estado de indefención originado por la falta de una inmediata citación al demandado en el juicio de alimentos de niños. - Guerrero Paccha, Diana Dolores (2014)
Often tend to find problems with the adoption and implementation of new legal reforms bodies or raised existing codes , therefore , this study is aimed at analyzing the legal problem constituted by the nimble lack of citation on the defendant in the trial of food, that according to Art will unnumbered 8 of the Código de la Niñez y Adolescencia alimony must be paid from the filing of the lawsuit and the absence of express provision of the law on the time that has complied with the summons to the defendant , is likely when there are overdue pensions practice , and in the case of being two , the actor can use the suit for collection , thus injuring the right to legal defense and security of the driven part .